CCCDTD5 recommendations on early non cognitive markers of dementia: A Canadian consensus. Issue 1 (17th October 2020) - Montero‐Odasso, Manuel; Pieruccini‐Faria, Frederico; Ismail, Zahinoor; Li, Karen; Lim, Andrew; Phillips, Natalie; Kamkar, Nellie; Sarquis‐Adamson, Yanina; Speechley, Mark; Theou, Olga; Verghese, Joe; Wallace, Lindsay; et al.
Abstract: Introduction: Cognitive impairment is the hallmark of Alzheimer's disease (AD) and related dementias. However, motor decline has been recently described as a prodromal state that can help to detect at‐risk individuals. Similarly, sensory changes, sleep and behavior disturbances, and frailty have been associated with higher risk of developing dementia. These clinical findings, together with the recognition that AD pathology precedes the diagnosis by many years, raises the possibility that non‐cognitive changes may be early and non‐invasive markers for AD or, even more provocatively, that treating non‐cognitive aspects may help to prevent or treat AD and related dementias. Methods: A subcommittee of the Canadian Consensus Conference on Diagnosis and Treatment of Dementia reviewed areas of emerging evidence for non‐cognitive markers of dementia. We examined the literature for five non‐cognitive domains associated with future dementia: motor, sensory (hearing, vision, olfaction), neuro‐behavioral, frailty, and sleep. The Grading of Recommendations Assessment, Development, and Evaluation system was used to assign the strength of the evidence and quality of the recommendations. We provide recommendations to primary care clinics and to specialized memory clinics, answering the following main questions: (1) What are the non‐cognitive and functional changes associated with risk of developing dementia? and (2) What is the evidence that sensory, motor, behavioral, sleep, and frailty markers can serve as potential predictors of dementia? Results: Evidence supported that gait speed, dual‐task gait speed, grip strength, frailty, neuropsychiatric symptoms, sleep measures, and hearing loss are predictors of dementia. There was insufficient evidence for recommending assessing olfactory and vision impairments as a predictor of dementia. Conclusions: Non‐cognitive markers can assist in identifying people at risk for cognitive decline or dementia. These non‐cognitive markers may represent prodromal symptoms and several of them are potentially amenable to treatment that might delay the onset of cognitive decline.